2023
DOI: 10.1371/journal.pone.0292463
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and understanding the care pathway of patients with atrial fibrillation in Brazil and the impact of the COVID-19 pandemic: A mixed-methods study

Alessandra C. Goulart,
Ana C. Varella,
Tiffany E. Gooden
et al.

Abstract: Background Atrial fibrillation (AF) is a major risk factor for stroke. To enable improvements to AF diagnosis and follow-up care, understanding current patient pathways and barriers to optimal care are essential. We investigated the patient care pathways and their drivers, and the impact of the COVID-19 pandemic on patient pathways in a middle-income country setting, Brazil. Methods This mixed-methods study in São Paulo, included adults (≥18y) with AF from 13 primary/secondary healthcare facilities. Surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…Our previous research found that patients with AF must travel far distances to receive care at the Jaffna Teaching Hospital and is a barrier to optimal care (in pre-pandemic times), particularly for rural inhabitants 36 . Similar findings have been highlighted in our research in Brazil, indicating that access to INR tests is an issue in other LMICs 37 . NOACs can be an effective alternative for the warfarin especially in LMICs where there are limited INR facilities, however, the costs of NOACs are hindering their introduction in Sri Lanka and many other low or lower-middle-income countries 4 .…”
Section: Discussionsupporting
confidence: 91%
“…Our previous research found that patients with AF must travel far distances to receive care at the Jaffna Teaching Hospital and is a barrier to optimal care (in pre-pandemic times), particularly for rural inhabitants 36 . Similar findings have been highlighted in our research in Brazil, indicating that access to INR tests is an issue in other LMICs 37 . NOACs can be an effective alternative for the warfarin especially in LMICs where there are limited INR facilities, however, the costs of NOACs are hindering their introduction in Sri Lanka and many other low or lower-middle-income countries 4 .…”
Section: Discussionsupporting
confidence: 91%
“…Our previous research found that patients with AF must travel far distances to receive care at the Jaffna Teaching Hospital and is a barrier to optimal care (in pre-pandemic times), particularly for rural inhabitants 36 . Similar findings have been highlighted in our research in Brazil, indicating that access to INR tests is an issue in other LMICs 37 .…”
Section: Discussionsupporting
confidence: 91%